The Effect of Environmental Social Governance (ESG) Performance and Fair Value Hierarchy on Earnings Management - Nelson, Andesta Brilian; Rahman, Annisaa (Assets: Jurnal Akuntansi dan Pendidikan, 2025)
This study aims to analyze the effect of ESG performance and fair value hierarchy level 1, 2 and 3 on earnings management. The sample used was 201 company observations consisting of non-financial companies that had ESG scores on refinitiv eikon in 2018-2023. The analysis method used is multiple linear regression. The results of this study show that in model 1 ESG has no significant effect on earnings management, while in the second model ESG has a significant negative effect on earnings management, so an additional test is conducted which shows that ESG has a significant negative effect on the two directional values (positive and negative) of earnings management. Then, fair value hierarchy level 1 has a significant negative effect on earnings management and fair value hierarchy level 2 and 3 have a significant positive effect on earnings management. These findings imply that sustainability performance and fair value measurement have a strategic role in reducing earnings management practices. This research contributes to improving the quality of financial reporting and ESG disclosure for companies.